THE ASSESSMENT OF THE ORTHODONTIC MINI-IMPLANTS RISK OF FRACTURE - A LITERATURE REVIEW - Panaite Tinela; Olteanu Daniel-Nicolae; Balcoş Carina Ana-Maria; Nikolaos Karvelas; Carmen Savin; Cristian Romanec; Ionut Luchian; Irina-Nicoleta Zetu (Romanian Society of Oral Rehabilitation, 2022)
A modern method of anchorage provision, orthodontic mini-implants appear to provide a number of advantages for both complex and anchorage-demanding orthodontic cases. This review aimed to collect data about the risk of fracture of the mini-implants in orthodontics. The main topic in the mini-implant studies is addressed to the risk of fracture because of the inappropriate selection of mini-implants from the point of view of diameter, length, type of alloy, or insertion angle.